Water allocation using system dynamic modelling in the aquaculture integrated with small-scale irrigation systems in Malawi. (February 2023) - Chunga, Brighton Austin; Marx, Walter; Cai, Xueliang; de Clercq, Willem; Watson, Andrew; Malota, Mphatso
Abstract: The agricultural sector is faced with numerous challenges including climate change and water scarcity in many developing countries. In order to address scarcity and improve water use efficiency for rural farmers, fish farming is being integrated with small-scale irrigation. However, there are challenges in how to allocate water between the two farming enterprises. This study explored the capabilities of system dynamics to allocate water between a fish pond and a crop field in Chingale, Malawi using a system dynamic software, Vensim™ PLE. For soil water and pond water, a simple water balance structure was built and connected to the crop growth structure. Simulations run for 125 days corresponding to the maize growth period. Model results are similar to the actual yield (about 3.5 ton/ha for hybrid) and biomass production (about 7 ton/ha) in the area. Results also show it was possible to maintain pond water depth at recommended depths for raising fish: fish stocking (1 m), operation of the pond (1.5–2.0 m) and harvesting of the fish (less than 1.2 m) throughout the maize growing period. While the study did not comprehensively build and simulate fish growth, the use of such simple tools would benefit rural farmers with few resources. Based on the promising capabilities and the results of the tool it is recommended that further comprehensive analysis to fully incorporate all key sub-components affecting crop and fish growth be carried out. Highlights: Small-scale rural farmers contribute to food security in most developing countries. SD explored with capability of allocating water between fish pond and crop field. Vensim software was used to develop a water allocation tool. Pond water balance and crop growth were successfully simulated. Simple tools help farmers to allocate water and increase resource use efficiency.